Food supplementation affects gut microbiota and immunological resistance to parasites in a wild bird species. Issue 3 (3rd February 2020) - Knutie, Sarah A.
Abstract: Supplemental feeding can increase the overall health of animals but also can have varying consequences for animals dealing with parasites. Furthermore, the mechanism mediating the effect of food supplementation on host–parasite interactions remains poorly understood. The goal of the study was to determine the effect of food supplementation on host defences against parasitic nest flies and whether host gut microbiota, which can affect immunity, potentially mediates these relationships. In a fully crossed design, I experimentally manipulated the abundance of parasitic nest flies Protocalliphora sialia and food availability then characterized the gut microbiota, immune responses and nest parasite abundance of nestling eastern bluebirds Sialia sialis . Food supplemented birds had 75% fewer parasites than unsupplemented birds. Parasite abundance decreased throughout the breeding season for unsupplemented birds, but abundance did not change throughout the season for supplemented birds. Food supplementation increased overall fledging success. Parasitism had a sublethal effect on blood loss, but food supplementation mitigated these effects by increasing parasite resistance via the nestling IgY antibody response. Food supplementation increased the gut bacterial diversity in nestlings, which was negatively related to parasite abundance. Food supplementation also increased the relative abundance of Clostridium spp. in nestlings, which was positively related to their antibody response and negatively related to parasite abundance. Synthesis and applications . Overall, the results of this study suggest that food supplementation, especially early in the breeding season, increases resistance to parasitism during the early life stage of the host, which might be mediated by the gut microbiota. Wildlife food supplementation is a common pastime for humans worldwide and therefore it is important to understand the consequences of this activity on animal health. Furthermore, supplemental feeding could induce resistance to detrimental parasites (e.g. invasive parasites) in hosts when management of the parasite is not immediately possible. Abstract : Overall, the results of this study suggest that food supplementation, especially early in the breeding season, increases resistance to parasitism during the early life stage of the host, which might be mediated by the gut microbiota. Wildlife food supplementation is a common pastime for humans worldwide and therefore it is important to understand the consequences of this activity on animal health. Furthermore, supplemental feeding could induce resistance to detrimental parasites (e.g. invasive parasites) in hosts when management of the parasite is not immediately possible. Image credit: Becky Boyd.